Desain Tapak Perencanaan PenangkaranKupu-Kupu di Kampus IPB Darmaga Menggunakan Sistem Zonasi untuk Mendukung Aktivitas Wisata Alam - maiser syaputra (Fakultas Kehutanan Universitas Winaya Mukti, 2020)
Butterfly captivity can be successful if there are artificial environmental conditions that are suitable for the life and reproduction of butterflies. Apart from the technical side, the success key of the captivity also determined from the side of site plan. Site planning is the ability to collect and interpreting data, project into the future, identify problems and provide a reasoned approach to solving existing problems. The purpose of this study was to design a captive development site for the IPB Dramaga butterfly captivity based on the conditions and characteristics of the area. The method used in this research consists of literature study, interview and observation. Data analysis consisted of six stages, consists of: preparation, inventory, analysis, synthesis, planning and design. The results of this study were the IPB Dramaga butterfly captivity site was designed into three zoning systems according to the needs of captive management, namely an office zone (0.37 ha), breeding zone (1.75 ha) and a tourism zone (2.13 ha).